Islamic capital markets and products : managing capital and liquidity requirements under Basel III - Archer, Simon; Abdel Karim, Rifaat Ahmed (John Wiley & Sons Ltd, 2018)
Includes three illustrative case studies that bring the covered material to life, this book is the definitive guide to the products offered in the Islamic capital markets (ICM), along with their legal and regulatory requirements. --